2015
DOI: 10.1089/ars.2014.6106
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Glutamate Oxaloacetate Transaminase as a Therapeutic Target Against Ischemic Stroke

Abstract: Significance: Glutamate serves multi-faceted (patho)physiological functions in the central nervous system as the most abundant excitatory neurotransmitter and under pathological conditions as a potent neurotoxin. Regarding the latter, elevated extracellular glutamate is known to play a central role in ischemic stroke brain injury. Recent Advances: Glutamate oxaloacetate transaminase (GOT) has emerged as a new therapeutic target in protecting against ischemic stroke injury. Oxygen-sensitive induction of GOT exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 99 publications
0
31
1
Order By: Relevance
“…Glutamate is positioned to serve as an ideal metabolic substitute given its sequestration in neurons and the need to mitigate neurotoxic accumulation under pathophysiological conditions such as ischemic stroke. As a transaminase, GOT catalyzes the transfer of the amino group from glutamate to the 4‐carbon TCA cycle intermediate oxaloacetate to generate aspartate and the 5‐carbon TCA cycle intermediate α‐ketoglutarate (2). This ability enables the anaplerotic flux of GOT‐metabolized glutamate into a truncated TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Glutamate is positioned to serve as an ideal metabolic substitute given its sequestration in neurons and the need to mitigate neurotoxic accumulation under pathophysiological conditions such as ischemic stroke. As a transaminase, GOT catalyzes the transfer of the amino group from glutamate to the 4‐carbon TCA cycle intermediate oxaloacetate to generate aspartate and the 5‐carbon TCA cycle intermediate α‐ketoglutarate (2). This ability enables the anaplerotic flux of GOT‐metabolized glutamate into a truncated TCA cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Krebs observed that glutamate was the only amino acid that increased cellular respiration in the cortex of rabbit brain under hypoglycemic conditions (5). Given the pathophysiological role of glutamate‐mediated neurotoxicity and cell death in ischemic stroke injury (7) and in light of our observation that SO‐mediated induction of GOT protects against ischemic stroke injury (24), we hypothesize that GOT can utilize otherwise neurotoxic glutamate to support cell survival in the face of ischemia‐induced hypoglycemia. The current study is designed to test the significance of GOT‐mediated glutamate metabolism in neural cell culture and the hypoglycemic stroke‐affected brain.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Oxaloacetate was recently introduced as a neuroprotective drug [19-22] due to ability to decrease blood glutamate levels by the activation of the blood-resident enzyme glutamate-oxaloacetate transaminase (GOT). This enzyme catalyzes, by transfer of an amino group, the transformation of glutamate into α-ketoglutarate and of oxaloacetate into L-aspartate.…”
Section: Discussionmentioning
confidence: 99%